Physical Condition of Mother and Children Aged Less Than Five Years in Public Health Center Depok III, Sleman, Yogyakarta - Etri Wahyuni; Wibowo Wibowo (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Background: Nutritional status and health of mother and child as a determinant of the quality of human being. The period of a thousand days of life is a sensitive period for the impact of the baby at this time that will be permanent and not be corrected. Nutritional status of children is influenced by several factors, that is genetic and environmental factors. Family factors also have an important role, which the mother has a role in the childcare. It is an expectation that the nutritional status of mother as known as one of the impact of the nutritional status of children can be particularly efforts in a thousand days of life. Objective: To find out the relationship between physical condition of toddler’s mother with the physical condition of toddlers in Puskesmas Depok III Sleman Yogyakarta. Methods: This was a cross sectional research, done in the Public Health Center Depok III, Sleman, Yogyakarta. Samples of this research was 104 toddlers. The research variables were the physical condition of toddler’s mother (height and nutritional status) and the physical condition of toddlers (based on nutritional status of index height/age, weight/age, weight/height, and BMI/age). Chi square test was used to do a hypothesis test. Result: Short and very short toddlers were 28.8%, based on the index of weight/age 7.7% were malnutrition and 2.9% were fat toddlers. Based on the index of weight/height 3.8% were very slim and skinny and 14.4% were fat, and based on the index of BMI/age 4.8% were very slim and skinny and 12.5% were obese. As much as 40.4% toddlers mother’s height ≤150 cm (short) and 59.6% of normal category. P-value for the relationship between height and toddler’s nutritional status, based on index of height/age was 0.135, p-value for relationship between mother’s nutritional status and toddler’s nutritional status, based on index of weight/age was 0.894, the index of weight/height was 0.929, and the index of BMI/age was 0.932, with no relationship between all of them. Conclusion: There was no significant relationship between mother height nutritional status of toddlers with an index based on height/age. There was no significant relationship between mother nutritional status and toddlers nutritional status based on the index of weight/age, weight/height, or BMI/age. Keywords: Nutritional status, Mother’s height